Evaluation of the olivocochlear efferent reflex strength in the susceptibility to noise-induced hearing loss - Soer, Maggi E. (Magdalena Elizabeth) (University of Pretoria, 2021)
Dissertation (MCommunication Pathology (Audiology))--University of Pretoria, 2021.